High-resolution bathymetry coupled with 3D models of hydrothermal vents from opportunistically-acquired imagery: Aurora vent field, Arctic Ocean - Tea Isler; Michael Jakuba; Tom Kwasnitschka; Autun Purser; Andrew Klesh; Vera Schlindwein; Christopher R. German (Journal of Maps)
Active venting at the Aurora hydrothermal field was first located in 2014. In July 2023, the AUV/ROV Nereid Under Ice (NUI) expanded the known size of the Aurora hydrothermal field, discovering 7 ‘black smokers’ together with associated lower-temperature flow. In this study, we present a new high-resolution bathymetric map acquired from NUI which has allowed us to identify morphological features previously undetectable from ship multibeam. All known active vents are aligned along a single 230 m-long ridge, parallel to the Gakkel Ridge strike direction and intersected by a scarp following the general trend of the Lena Trough. The new vents were measured at up to 17 m height from 3D models generated using structure-from-motion techniques applied to opportunistically acquired imaging data collected while in exploration mode. The extent of extinct sulfides present, together with the towering height of vents are consistent with a period of sustained high-temperature venting at Aurora.